Nitrogen fertilisation of boreal forest soil increases soil carbon pool through elevated microbial necromass formation but also modifies tree secondary metabolism - Adamczyk, Bartosz; Adamczyk, Sylwia; Tupek, Boris; Li, Qian; Martinovic, Tijana; Richy, Etienne; Lehtonen, Aleksi; Baldrian, Petr; Mäkipää, Raisa (Elsevier, 2025)
Forests contain significant amounts of the global carbon (C) pool with the major fraction stored belowground. Nitrogen (N) fertilisation of forest soils may increase biomass production and soil organic C pools, providing a strategy for climate change mitigation. Here we aimed to elucidate the mechanisms behind the increase in soil C due to N addition using a long–term fertilisation experiment on a Scots pine stand with a combination of chemistry, microbiology and greenhouse gas fluxes. Our results showed that N fertilisation increased C stocks, microbial biomass, necromass and the activity of extracellular enzymes, with no significant increase in greenhouse gas production. Moreover, N fertilisation decreased the production of a group of plant secondary metabolites, tannins. These profound changes were observed in the organic layer of the soil, and differences in mineral soil were less detectable. Mechanistically, N fertilisation increased the C stock via elevated litter input and higher transfer of root C to soil microorganisms increasing fungal biomass and further necromass, which was stabilised in the soil. Our study supports the view that management strategies to increase microbial necromass in persistent C pools could lead to elevated C stabilization, though caution should be taken regarding potential changes in plant metabolism.
Keywords: C cycle; C stabilization; enzymatic activity; forests; fungi; N cycle